Exploring Literary Psychology: Unveiling the Archetypes of Secondary Characters in Tere Liye's Novel 'Hujan' - Arju Susanto; Mohammad Darwis; Lana Nadia; Kurnia Rachmawati; Nisrina Rona Nabilah (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
In literature, characters often reflect real-life individuals, sometimes resembling people known to the author. Likewise, literary settings may mirror real-world environments, creating a sense of familiarity and authenticity within the narrative. The inclusion of authentic elements, particularly genuine human characters, in literary compositions renders them subjects for psychological examination. Such works serve as psychological reflections of the author while also exerting psychological influence on the reader. For instance, the novel "Hujan" recounts the life journey of a young girl named Lail. In accordance with the title of the novel, every important moment that occurs in Lail always has an atmosphere or connection to rain. Lail as the main character in this novel has a fairly ordinary character with a personality type like that of young girls in general. This research aims to describe the structure of the novel "Hujan" by Tere Liye and describe the archetype of the character Lail based on Jung's analytical psychology theory using qualitative descriptive research methods. The data collection techniques used in this research are reading, listening and note-taking techniques. This research produces the structure of the novel "Hujan" by Tere Liye in the form of intrinsic elements of the novel in the form of; 1) theme; 2) plot; 3) characterization; 4) background; and 5) point of view. Apart from that, this research also produces elements of the archetype of the character Lail in the novel "Hujan" by Tere Liye in the form of persona, shadow, animus, and self.